2019
DOI: 10.1002/hsr2.144
|View full text |Cite
|
Sign up to set email alerts
|

Community health promotion programs for older adults: What helps and hinders implementation

Abstract: Background and Aims Despite the many known health benefits of physical activity (PA), older adults are the least active citizens in many countries. Regular PA significantly decreases the odds of functional limitation and social disengagement. However, there is a dearth of publicly funded support services for older adults. The primary objective of this study is to conduct a formative evaluation to examine the implementation of community‐driven health promotion programs for older adults in British Columbia, Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
(87 reference statements)
2
19
0
Order By: Relevance
“…Existing studies have demonstrated that social isolation could diminish participation in recreational physical activity as well as induce anxious-depressive-related behaviors [ 9 ]. In addition, older adults who were at risk of social isolation did not seem to make full use of medical services or seek help from others [ 10 ]. A vicious circle can be created between social isolation and a low level of health-promoting behaviors, which may finally lead to adverse health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have demonstrated that social isolation could diminish participation in recreational physical activity as well as induce anxious-depressive-related behaviors [ 9 ]. In addition, older adults who were at risk of social isolation did not seem to make full use of medical services or seek help from others [ 10 ]. A vicious circle can be created between social isolation and a low level of health-promoting behaviors, which may finally lead to adverse health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…88 92 In addition, we found that facilitating access to interventions in the form of transportation or affordability is a crucial component, as found by other reports. 93 We also found that participants' and professionals' poor understanding of referral pathways, lack of fit between intervention components and participant interest, age-related limitations and the fear of joining new groups, were barriers that affected overall intervention uptake and acceptability. Interventions should be adapted to participants' age-related physical and mental health conditions and social needs.…”
Section: Discussionmentioning
confidence: 79%
“…46 The participants' positive relationship with their activity coach and interactions with other participants influenced feelings of social connectedness during CTM. 47,48 Sharing information and experiences, learning from their peers, and engaging with others who share familiar experiences also contributed to feelings of social connection. 35 It seems imperative to maintain social and mental health benefits; to do so, programs that support these outcomes must be ongoing.…”
Section: Discussionmentioning
confidence: 99%